Tribology of Diamond-Like Carbon Films Fundamentals and Applications - Donnet, Christophe; Erdemir, Ali.; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
Since their initial discovery, diamond-like carbon films have enjoyed an overwhelming interest from both the scientific and industrial communities. There now exist reliable models, computer simulations and experimental findings that clearly demonstrate their exceptional friction and wear properties. Tribology of Diamond-like Carbon Films discusses the most important structural, chemical, mechanical and tribological characteristics of DLC films, and emphasizes their applications in mechanical systems ranging in size from nano/micro (like MEMS, NEMS) to macro scale devices (like bearings, gears, aerospace mechanisms, various engine parts and components). The chapters of this book are particularly dedicated to the fundamental tribological issues that impact the performance and durability of these coatings in numerous industrial applications including automotive, microelectronic, aerospace, biomedical, and manufacturing. Written by some of the most prominent world experts representing academia, national laboratories, and industrial companies, Tribology of Diamond-like Carbon Films is an important book for researchers and engineers.
General Overview on DLC Coatings -- Classification of Diamond-like Carbons -- Non-destructive Characterisation of Carbon Films -- Mechanical Characterisation and Properties of DLC Films -- Residual Stresses in DLC Films and Adhesion to Various Substrates -- Tribology of DLC Coatings Fundamentals and Experimental Studies -- Fundamentals of the Tribology of DLC Coatings -- Environmental and Thermal Effects on the Tribological Performance of DLC Coatings -- Third Bodies and Tribochemistry of DLC Coatings -- An Overview of Superlubricity in Diamond-like Carbon Films -- Hard DLC Growth and Inclusion in Nanostructured Wear-protective Coatings -- Environmental and Surface Chemical Effects on Tribological Properties of Carbon-based Coatings -- Triboemission and Triboplasma Generation with DLC Films -- Doping and Alloying Effects on DLC Coatings -- Tribology of Carbon Nitride Coatings -- Tribology of DLC Films Under Fretting Conditions -- Tribology of DLC Films Under Slip-Rolling Conditions -- Tribological Behavior of DLC Films in Various Lubrication Regimes -- Applications and Future Trends in DLC's Tribology -- Industrial Production of DLC Coatings -- DLC Films in Mechanical and Manufacturing Industry -- Wear Resistance of Amorphous DLC and Metal Containing DLC in Industrial Applications -- DLC Films in Biomedical Applications -- Nanotribology of Ultrathin and Hard Amorphous Carbon Films -- Laser Processing of Tribological DLC Films: An Overview -- New Trends in Boundary Lubrication of DLC Coatings -- Fullerene-like Carbon Nitride: A New Carbon-based Tribological Coating.
Keywords: Materials science; Atoms; Physics; Continuum mechanics; Mechanical engineering; Industrial engineering; Nanotechnology; Tribology; Corrosion and anti-corrosives.; Coatings; Materials Science; Tribology, Corrosion and Coatings; Continuum Mechanics and Mechanics of Materials; Operating Procedures, Materials Treatment; Atomic, Molecular, Optical and Plasma Physics; Nanotechnology; Mechanical Engineering; Electronic books